Performance and working space requirement for passive and semiactive automobile suspension - Mohd. Jailani Mohd. Nor (1992)
In this paper computer simulation is used to study the performance of an automobile suspension system. The effect of tyre stiffness and unsprung mass on the performance in terms of riders comfort and the maximum working space requirement of the suspension system are also studied. Next, simple "on-off" semi-active control rules are applied to the damper. These rules have been able to reduce the maximum working space required when compared to the passive suspension system. But, in terms of riders comfort the passive system is more superior. Finally, modified control rules are introduced and comparison on the performance and working space requirement are made with the suspension systems mentioned earlier. In general, the modified control rules have been able to increase riders comfort but larger working space are required